Factors Affecting The Conversion Of Cocoa Farming Land Function To Paddy Fields Farming In Penanggo Jaya Village, Lambandia District, East Kolaka regency - Faustina Putri Rasali; Abdi, Abdi; Rosmawaty, Rosmawaty (International journal of technology and education research, 2023)
This study aims to determine the factors that influence the conversion of cocoa farming land function to lowland paddy fields farming in Penanggo Village, Lambandia District, East Kolaka Regency. This research was conducted from November to December 2021. The research method uses quantitative descriptive. The selection of the location of this study was determined deliberately (purposively), taking into account that Penanggo Jaya Village has a number of farmer households that have transferred cocoa land to paddy fields. The population in the study numbered 392 people. The sampling technique uses the Slovin formula with an error degree (α) of error of 15%. The number of respondents was 72 people. The data analysis used in this study is Logistic Regression Analysis, steps in testing assessing the overall model (overall model fit/G test), assessing the feasibility of the regression model and wald test (partial). The results showed that pest and disease attacks of 0.030 < 0.05 and production yields of 0.000 < 0.05, these two variables have a significant chance of influencing the decision of farmers to transfer cocoa land to paddy rice crops, while plant age, land area and infrastructure have no chance of influencing farmers' decisions to transfer cocoa land to paddy field crops.The results of this study indicate that with the transfer of community land in Penanggo Village, Lambandia District, East Kolaka Regency, they can meet and increase their economy.